2022
DOI: 10.1142/s0219887822500621
|View full text |Cite
|
Sign up to set email alerts
|

Emerging hyperbolic spaces and some considerations in AdS cosmology

Abstract: Recently, PNDP-manifolds have been introduced, and these have shown to be useful in applicative aspects especially in the field of cosmology, introducing a new geometric/topological approach to the concept of “emerging space”. However, the applications considered so far concern only trivial and flat PNDP-manifolds. Therefore, we show the existence of non-Ricci-flat solutions for PNDP-manifolds with positive “virtual” dimension which have hyperbolic [Formula: see text]-manifold. Based on this, we have advanced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…(In fact, in this circumstance, if we consider a Kuranishi neighborhood (R d , E, s), with manifold R d , obstruction bundle E → R d , and section s : R d → E, then the dimension of the derived manifold F is dim(R d ) − rank(E), see [13]), and for rank(E) = 2d, the manifolds considered would coincide with the PNDP-manifolds (see [14], [15] and [16]). Therefore the existence of the solution shown above, for λ > 0, is also valid in the context of the PNDP-manifolds (in particular for PNDP-manifolds with positive virtual dimension), where its base-manifold is the product between two conformal manifolds to a n -dimensional and n-dimensional pseudo-Euclidean space, respectively.…”
Section: Conformal B-metricsmentioning
confidence: 99%
“…(In fact, in this circumstance, if we consider a Kuranishi neighborhood (R d , E, s), with manifold R d , obstruction bundle E → R d , and section s : R d → E, then the dimension of the derived manifold F is dim(R d ) − rank(E), see [13]), and for rank(E) = 2d, the manifolds considered would coincide with the PNDP-manifolds (see [14], [15] and [16]). Therefore the existence of the solution shown above, for λ > 0, is also valid in the context of the PNDP-manifolds (in particular for PNDP-manifolds with positive virtual dimension), where its base-manifold is the product between two conformal manifolds to a n -dimensional and n-dimensional pseudo-Euclidean space, respectively.…”
Section: Conformal B-metricsmentioning
confidence: 99%
“…Even the Weyl tensor arises from dimensions. According to a valid definition of the term "virtual dimension", A. Pigazzini et al presented PNDP-manifolds, in [1,2,3,4,5,6,7], which have since shown to be extremely adaptable from an implementation perspective in a number of various research areas. For models of PNDP-manifolds, with positive, zero and negative "virtual dimensions" the authors of the works previously mentioned have shown the possibility of using these as well as their interpretation.…”
Section: Introductionmentioning
confidence: 99%